Unintended consequences of changes to lung allocation policy. Issue 8 (18th March 2019) - Puri, Varun; Hachem, Ramsey R.; Frye, Christian Corbin; Harrison, Margaret Shea; Semenkovich, Tara R.; Lynch, John P.; Ridolfi, Gene; Rowe, Casey; Meyers, Bryan F.; Patterson, George Alexander; Kozower, Benjamin D.; Pasque, Michael K.; et al.
Abstract : Organ allocation for transplantation aims to balance the principles of justice and medical utility to optimally utilize a scarce resource. To address practical considerations, the United States is divided into 58 donor service areas (DSA), each constituting the first unit of allocation. In November 2017, in response to a lawsuit in New York, an emergency action change to lung allocation policy replaced the DSA level of allocation for donor lungs with a 250 nautical mile circle around the donor hospital. Similar policy changes are being implemented for other organs including heart and liver. Findings from a recent US Department of Health and Human Services report, supplemented with data from our institution, suggest that the emergency policy has not resulted in a change in the type of patients undergoing lung transplantation (LT) or early postoperative outcomes. However, there has been a significant decline in local LT, where donor and recipient are in the same DSA. With procurement teams having to travel greater distances, organ ischemic time has increased and median organ cost has more than doubled. We propose potential solutions for consideration at this critical juncture in the field of transplantation. Policymakers should choose equitable and sustainable access for this lifesaving discipline. Abstract : An analysis of institutional as well as national data indicates that patients transplanted since the lung allocation policy change have largely comparable disease severity, though the cost of donor lungs has increased substantially due to more organs being procured from distant organ procurement organizations. See the editorial from Lehman and Chan on page 2151 .